2014
DOI: 10.2466/15.03.pr0.114k26w6
|View full text |Cite
|
Sign up to set email alerts
|

Depressive Rumination and Past Depression in Japanese University Students: Comparison of Brooding and Reflection

Abstract: Summary .-The Ruminative Responses Scale, a measure of depressive rumination, contains two subscales: Brooding and Refl ection. Treynor, Gonzalez, and NolenHoeksema (2003) proposed that Brooding is maladaptive and Refl ection is adaptive. This article examined the relationships among Brooding, Refl ection, and previous depression in two samples of Japanese undergraduates, who were non-depressed at the time of their participation. Based on answers to a self-report measure, participants were divided into a form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 55 publications
1
5
0
Order By: Relevance
“…Our sample reported higher average levels of repetitive negative thinking than those observed in the two studies we sought to replicate (Koval et al, 2016 ; Onie & Most, 2017 ), and in other undergraduate samples (e.g., Hasegawa, 2013 ; Koval et al, 2012 ; Onie & Most, 2021 ; Topper et al, 2014 ). In fact, the current sample’s rumination levels were comparable to participants that were previously or currently depressed (Hasegawa et al, 2014 ; Koval et al, 2012 ).…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Our sample reported higher average levels of repetitive negative thinking than those observed in the two studies we sought to replicate (Koval et al, 2016 ; Onie & Most, 2017 ), and in other undergraduate samples (e.g., Hasegawa, 2013 ; Koval et al, 2012 ; Onie & Most, 2021 ; Topper et al, 2014 ). In fact, the current sample’s rumination levels were comparable to participants that were previously or currently depressed (Hasegawa et al, 2014 ; Koval et al, 2012 ).…”
Section: Discussionsupporting
confidence: 54%
“…Fifth, given that the brooding component of rumination is considered particularly maladaptive (e.g., Hasegawa et al, 2014 ) and has been found to correlate most strongly with emotional inertia (Koval et al, 2012 ), we re-ran analyses that involved repetitive negative thinking using only the brooding subscale of the Ruminative Response Scale to represent rumination (Table S6 ). Our H1 and H2 findings did not change.…”
Section: Resultsmentioning
confidence: 99%
“…Interventions targeting rumination that have shown decreases in depressive symptomology among mildly depressed or dysphoric populations were typically employed over multiple weeks (e.g., Watkins et al, 2012). Research has shown that the brooding subtype of rumination, which decreased significantly in the current study, is associated with experiencing depression in the past (Hasegawa et al, 2014), at the present time (Raes et al, 2011;Whitmer & Gotlib, 2011), and in the long term (Schoofs et al, 2010;Treynor et al, 2003). Since brooding was reduced in the current study, it seems promising that depression could be reduced as a result of this type of intervention.…”
Section: Discussionmentioning
confidence: 84%
“…[1][2][3][4][5][6][7][8][9][17][18][19][20][21][22][23][24][25][26] This approach reduces CR to an object of empirical investigation exclusively.…”
Section: Methodsmentioning
confidence: 99%
“…Hasegawa et al 19 Repetitive and passive thinking about one's symptoms of depression and possible causes and consequences of these symptoms.…”
Section: Definitions Of Cognitive Rumination Phenomenological Aspectsmentioning
confidence: 99%